KESINAMBUNGAN DATA REKAM MEDIS TERKAIT SISTEM PENYIMPANAN DESENTRALISASI DI PUSKESMAS JETIS 1 BANTUL - , TITI WAHYUNI; , Dra. Rawi Miharti., MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Medical records have benefits as a communication tool, where all the action and the care given by health workers should be based on and refers to the history of the care given to the patient once before. Record-keeping, inpatient and outpatient care in the use of separate storage and file medical records, inpatient and outpatient medical records are not used in tandem. Thus, in the treatment of patients who subsequently had difficulty dikarena doctor doctors knew the patient's previous history. Objective: Knowing the maintenance of medical records file storage inpatient and outpatient medical records in the health center Jetis 1 Bantul, and to know the sustainability factor in the health center medical records Jetis 1 Bantul. Methods: The study was a descriptive, cross-sectional qualitative design. Retrieval of data through observation and interviews. Subjects in this study amounted to 6 people is made up of officers outpatient medical record 1 officer, 1 nutrition officer, and 1 physician, inpatient staff consists of 1 nurse and 1 physician and Head of Puskesmas as triangulation. Objects in this study is the management of file storage inpatient medical records storage and management of outpatient medical record file. Results: File Handling inpatient medical records stored by chronological and not given medical record number so that officers difficulties in the recovery of the file. While the outpatient medical record file is stored by the storage system family and straight numerical filing folders. But outpatient medical record file is not given area code. In practice, medical record file hospitalization and outpatient medical record file is not used as a further consideration of the treatment of patients. Factors that cause discontinuities in the health center medical records Jetis 1 Bantul is a factor procedures and human resources (HR). Factors associated procedures in the absence of fixed procedure record file storage and retrieval of medical inpatient and outpatient care as well as the numbering of the inpatient medical record. Whereas HR factors associated with lack of knowledge and perception of officers lacking proper officers of the storage system.